The mediating influence of place attachment in the relationship between affective image and customer’s psychosocial well-being towards revisit intention on co-working spaces in Metro Manila, Philippines - Aleah Mae V. Quindoza; Nicole Anne A. Mercado; Edrian C. Peña; Mark Chris M. Lapuz (Journal of Rural Tourism, 2026)
Purpose - This study aims to investigate the mediating role of place attachment in the relationship between affective image and customers’ psychosocial well-being, and how these factors influence revisit intention in coworking spaces in Metro Manila. Methodology/Design/Approach - A quantitative research design was employed, with data collected from 271 regular users of coworking spaces featuring coffee lounges. Structural equation modeling (SEM) was applied to test the relationships among affective image, place attachment, psychosocial well-being, and revisit intention. Findings - The results reveal that affective image has a positive impact on place attachment and psychosocial well-being. However, the mediating role of place attachment between affective image and psychosocial well-being was not statistically significant. Originality/Value - The study underscores the importance of both environmental and social factors in shaping customer experiences. For coworking spaces, balancing functional design with emotionally engaging features is essential to enhance customer satisfaction and foster revisit intentions.